Travelers’ malaria-related knowledge, attitudes and behavior on the north coast of Peru - Iglesias-Osores, Sebastian; Saavedra-Camacho, Johnny Leandro; Failoc-Rojas, Virgilio E (Revista Cubana de Medicina Tropical, 2021)
Introduction: An increase in interprovincial travel has been registered annually during the last decade on the north and northeast coast of Peru, resulting in the spread of vector-borne diseases such as malaria. Therefore, travelers using interprovincial transport should be informed about the impact of infectious diseases in endemic regions and be aware of the risk of acquiring a travel-related condition. Objective: Examine travelers’ malaria-related knowledge, attitudes, and practices. Methods: A cross-sectional study was conducted from January to March 2019 of a random sample of individuals who attended bus stations classed as areas with a higher risk of malaria selected at random in Chiclayo, Peru. The study was conducted reliably through a survey consisting of 29 questions: 18 about knowledge and 11 about attitudes. Results: Of the 250 participants in the study, knowledge was found to be good in 29.13%, practices in 14.74%, and attitudes in 18.33%. People with a higher education degree had a better level of knowledge and attitudes. Also, 60 people were asked about their self-perception of knowledge about malaria and said their knowledge about the subject was adequate. Of the 190 who reported not having enough knowledge about malaria, 49.47% were interested in learning about malaria practices and 25.26% were interested in learning about treatment. Conclusions: Most of the knowledge, attitudes, and practices of people who travel to endemic areas are not adequate.